Moving towards Entrepreneurial Translator Education: a Review of Entrepreneurship Competence in Spanish Translator Education Programmes - Veiga Díaz, Maite (HERMES - Journal of Language and Communication in Business, 2020)
This paper reviews the entrepreneurship competences included in the curricula of undergraduate translation and interpretation degrees in Spain to determine whether they explicitly or implicitly match the competences included in the EntreComp framework. Our review reveals that the EntreComp entrepreneurial competences are underrepresented in current curricula in Spain, with some remarkable exceptions, particularly regarding the ‘resource management’ and ‘learning by doing’ competences. The SWOT analysis performed using the results derived from the descriptive analysis of the collected data suggests that the spotted strengths and opportunities can compensate for most of the weaknesses. Accordingly, it is our claim that an entrepreneurial approach to education that is compatible with the Entrepreneurship 2020 Action Plan can be introduced in Spanish translator education programmes within the current framework.